2011
DOI: 10.1021/jp2055156
|View full text |Cite
|
Sign up to set email alerts
|

Photophysics of n-Butyl-Capped Silicon Nanoparticles

Abstract: The photophysical properties are described of silicon nanoparticles protected with a shell of n-butyl chains, and with an asymmetric size distribution with a peak between 2 and 3 nm, and a tail extending up to 7 nm. The excited nanoparticles decay via multiexponential luminescence on a time scale of a few nanoseconds. Longer-lived nonluminescent dark states were observed by nanosecond transient absorption spectroscopy. The average lifetime of the luminescent excited states increased somewhat with increasing wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
15
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 74 publications
(119 reference statements)
2
15
0
Order By: Relevance
“…alkyl, alkenyl) moieties to the surface of silicon nanocrystals. 115,[175][176][177] Understanding the details of the mechanism of hydrosilylation is still the focus of intense studies and debates on bulk silicon surfaces, and much less work has been done with silicon quantum dots than bulk silicon. However, increasing evidence suggested that hydrosilylation on silicon nanocrystals happened in a comparable manner to flat or porous silicon 84,167,173 (Fig.…”
Section: Wet-chemical Based Modification Strategiesmentioning
confidence: 99%
“…alkyl, alkenyl) moieties to the surface of silicon nanocrystals. 115,[175][176][177] Understanding the details of the mechanism of hydrosilylation is still the focus of intense studies and debates on bulk silicon surfaces, and much less work has been done with silicon quantum dots than bulk silicon. However, increasing evidence suggested that hydrosilylation on silicon nanocrystals happened in a comparable manner to flat or porous silicon 84,167,173 (Fig.…”
Section: Wet-chemical Based Modification Strategiesmentioning
confidence: 99%
“…Fortunately, a wide array of synthetic methods has become available for the preparation of surface-functionalized Si and Ge NPs. 38, 39 Therefore, a comparative study is now possible, in which the toxicity of the different Si NPs and Ge NPs can be determined with respect to their surface characteristics. This can help to gain insight in how surface factors of these NPs can influence the toxicity, although n-alkyl terminated uncharged and water-insoluble Si NPs were also reported to show adequate cellular uptake without causing toxicity.…”
Section: Introductionmentioning
confidence: 99%
“…6,21,22 In order to stabilize SiQDs, procedures have been developed to functionalize the surface with groups that will protect from surface oxidation and render the QDs soluble for solution processing. 16,17,[23][24][25][26][27][28][29][30][31][32][33][34][35][36] Organic alkyl chains are one of the most common groups used to functionalize SiQDs through the formation of Si-C bonds using the hydrosilylation reaction of alkenes/alkynes with the Si-H functionalized surface. To date, the influence of alkyl chains on the optical properties of SiQDs is very limited and only small changes have been reported.…”
mentioning
confidence: 99%